2014
DOI: 10.1080/03601277.2014.974386
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equation Model of the Factors Affecting Morale of a Select Group of Filipino Elderly in a Community Setting

Abstract: While morale among the elderly has been widely and extensively studied, results are varied and at times conflicting. Hence, the purpose of this study is to explore the factors affecting elderly morale of a select group of Filipinos in a community setting. A 64-item questionnaire was utilized to survey 323 Filipinos aged 60 and above residing in the National Capital Region of the Philippines in May 2013. Respondents completed a robotfoto, a checklist of chronic illnesses, and measures of the social support, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
4
7
0
Order By: Relevance
“…In contrast with some previous studies of morale and age [13,18], the level of morale was lower in the older age groups. e results from the present study are, however, in line with the study of de Guzman et al [12] and with several studies of measures of SWB, where lower levels of well-being have been noted among the oldest-old (e.g. [20]).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast with some previous studies of morale and age [13,18], the level of morale was lower in the older age groups. e results from the present study are, however, in line with the study of de Guzman et al [12] and with several studies of measures of SWB, where lower levels of well-being have been noted among the oldest-old (e.g. [20]).…”
Section: Discussionsupporting
confidence: 93%
“…Further, it is evident that the relationship between healthrelated variables and morale in old age is complex, especially considering that different studies have come to somewhat conflicting results. Mancini and Quinn's study (1981) found no associations between morale and for example the use of medical services or the number of illnesses, while the history of hospitalization in the study of Iwasa et al (2006) and the number of chronic illnesses in the study of de Guzman et al (2015) were found to be associated with lower morale. The differing results might partly be explained by the use of different measurements of illness and differences in methodology.…”
Section: Introductionmentioning
confidence: 93%
“…In Litwin's (2001) study, individuals with more restricted social networks had lower morale than those with broad social networks that included family, friends and neighbors. Lower social support (de Guzman et al 2015;Loke et al 2011) and living alone (Iwasa et al 2006) have further been associated with lower morale. In samples of very old people, lower satisfaction with support from family (Deng et al 2010) and perceived loneliness (von Heideken Wågert et al 2005) have been associated with lower morale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations